Fe3+-substitution effect on the thermal variation of J–E characteristics and DC resistivity of quadruple perovskite CaCu3Ti4O12. (1st March 2022) - Modi, Kunal B.; Raval, Pooja Y.; Parekh, Dolly J.; Modi, Shrey K.; Joshi, Niketa P.; Makadiya, Akshay R.; Vasoya, Nimish H.; Joshi, Utpal S.
Abstract: The electrical properties of cubic perovskite series, CaCu3– x Ti4– x Fe2 x O12 with x = 0.0, 0.1, 0.3, 0.5, and 0.7, have been studied by employing current density as a function of electric field characteristics registered at different temperatures and thermal variations of direct current electrical resistivity measurements. All of the compositions exhibit strong non-ohmic behavior. The concentration dependence of breakdown field, the temperature at which switching action takes place, and maximum value of current density ( J max ) has been explained on account of structural, microstructural, and positron lifetime parameters. The highest ever reported value of J max = 327 mA/cm 2 has been observed for pristine composition. The values of the nonlinear coefficient advise the suitability of ceramics for low-voltage varistor applications. The Arrhenius plots show typical semiconducting nature. The activation energy values indicate that electric conduction proceeds through electrons with deformation in the system.